Economic analysis of land use: the case of East Hararghe administrative zone in Ethiopia - Worseme, Hassen Ibrahim (University of the Free State, 2004)
This study aimed at developing and applying a methodology for land use analysis through looking for a form of land use that provides sufficient and rising incomes to the agricultural population of East Hararghe Administrative Zone, and at the same time maintains the productive capacity as well as other environmental services of the land resources of the zone. The study starts with the elaboration of the problem statement, objectives, hypothesis and significance of the study. This is followed by the explanation of the approaches pursued in conducting the present study. The study area is also thoroughly described. The problem statement and the objectives of the study indicate that there exists a huge gap between zonal crop production and the population growth despite a substantial expansion of eropland in the zone. This implies the existence of numerous set backs in the land use system of the zone and necessitated a close investigation of the land use systems of the farming community of the study area in order to come up with an improved and efficient land use pattern that will overcome the acute land shortages as compared to the everincreasing population of East Hararghe Administrative Zone. The most important findings and results of this study are based on the literature study; the development of the research methodology; the description of the surveyed data that is obtained through questionnaire survey; and the analysis of the land use model of the study area. Land resource and land use was assessed from a global point of view. The problems that are associated with the use of the land resource in the developing countries were investigated. An extensive study was also carried out to introduce the agricultural sector of Ethiopia. The agricultural sector in Ethiopia is almost entirely dominated by small-scale, resource-poor farmers who produce 90 to 95 percent of all agricultural outputs. The role of economics within land use analysis is also reviewed. This role is elaborated through the discussion of a skeletal model of the agricultural sector; the concepts of regional agricultural planning, land evaluation and farming system analysis; the concepts of resource economics and land economics; and the issues of property rights and sustainable development. A linear programming model for the economic appraisal of the land use in the study area was presented following the description of the conceptual framework of the model. The different parts of the zonal linear programming model were discussed under the headings of objectives, variables and constraints. This was followed by the general formulation of the land use model of the zone called EASTHAR. The matrix of the model includes three sub-matrices each representing a different farm type. The farm types are distinguished on the basis of agro-ecological classification of the surveyed districts and peasant associations. The EASTHAR model was analyzed by using the GAMS software after it was extensively written in the GAMS programming language. Three land use scenarios are analysed to assess the effects of changes in factors that influence land use decisions and whether incomes of farms (fan increase through an improved land use. The results of the base scenario indicated that the incomes of farms can increase with improved land use pattern as the value of the objective function, or the economic surplus, is positive for the entire zone and for the different farm types. The model showed, how land has to be assigned to the different crops at zonal level and at each farm types level for maximizing farm incomes under proper and improved resource use. The most important staple food crops of the population of the zone are all incorporated in the optimum land use and the potential for specialization that can exist among the different farm types of the zone has also been indicated. A comparison of the results of the base scenario with the results of an opportunity cost scenario represented an important outcome of the model. The zonal economic surplus in the opportunity cost scenario is 33% lower than the base scenario. The valuation of the on-farm household labour thus has a negative effect on the incomes of the farm households. However, land use as well as labour, current input and draft power uses did not change from that of the base scenario. This shows that the mere valuation of the onfarm household labour will not automatically disturb land use decisions. An interesting outcome was observed when comparing the results of the base scenario with the results of a scenario of an assumed drought condition. The drought case scenario analyzes the consequences for land use in case drought occurs in the study area. Drought is a recurring problem of Ethiopians especially the rural population. The results of the analysis indicated that almost every land use defining variable was subject to change when drought occurs. According to these results, in a subsistence agriculture which is solely rain fed, a decline in the annual rainfall will undoubtedly lead to large reductions in the income of the farming population. Based on the results of the study important policy recommendations were outlined. The implementation of the envisaged improved land use patterns can have important impact in altering the poor income earning capacity of the farm households in the zone and have a better environmental impact. For farmers to produce the amount of grains required for home consumption and ensure their food security, there is a need to subsidize them to the amount of their lost gross margins during drought periods. Farmers must also be encouraged to save and have financial reserves for unforeseen adverse production conditions through the establishment of appropriate saving institutions to limit the subsidy. It may also be necessary for the government to approach donors to contribute to the subsidy, as this contribution will hopefully be lower than the cost of food aid in monetary terms. However, the dependence on food aid cannot be a preferable alternative and to supply enough food to the growing population of the region more food needs to be produced by the zone itself. This is because although other zones can produce food cheaply, for subsistence farmers who are producing crops mainly for home consumption (and not for the market) it is extremely hard (if not impossible) to engage in trade and rely on outputs produced in other zones.
Thesis (Ph.D. (Agricultural Economics))--University of the Free State, 2004
Keywords: Land use -- Ethiopia; Land use -- Economic aspects -- Ethiopia